Communicative Language Teaching (CLT) in Practice: A Case Study at English First Pajajaran Bogor 2025 - Kaifar Drajad Alkautsar; Retno Dwigustini (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
This study investigates how Communicative Language Teaching (CLT) is implemented at English First Pajajaran Bogor and evaluates its effectiveness in improving students’ communicative competence through classroom observations and teacher interviews. CLT is a widely recognized approach in language education that emphasizes real-life communication, interactive activities, and student-centered learning. The primary goal of CLT is to enhance learners’ ability to effectively communicate in real-life scenarios, fostering practical language skills rather than merely focusing on theoretical knowledge. The research aims to analyze how CLT is applied in English First Pajajaran Bogor, assess its effectiveness in enhancing students’ speaking, listening, and overall communication skills, and identify the challenges faced by both teachers and learners in its implementation. Using a qualitative research approach and a deductive method, the study collects data through classroom observations and interviews with teachers. The results indicate that CLT procedures, such as group discussions, games, dialogues, repetition, and question-and-answer sessions, positively impact students’ language proficiency, particularly in speaking and listening. These activities foster an interactive and engaging learning environment that encourages active student participation. However, these methods' success depends on adjusting teaching strategies to fit the students' specific needs and the limitations of the classroom environment, such as time constraints and available resources. Despite these challenges, the findings suggest that CLT significantly contributes to the development of students’ communicative competence when effectively implemented.